A Multi-volume constraint approach to diverse form designs from topology optimization. (15th March 2023) - Yan, Xin; Xiong, Yulin; Bao, Ding Wen; Xie, Yi Min; Peng, Xiangguo
Highlights: This paper detailly introduces the principle and process of multi-volume constraint approach based on BESO method. All the MV-BESO parameters and their effects are clearly discussed with some series of numerical examples. Several building components are introduced to present how to predesign local structural features into topology optimization. Abstract: Topology optimization methods gain extensive attention from many engineering fields for their capacities of meeting the diverse requirements of structural performances and innovative appearances. While most classical topology optimization techniques focus on globally optimal form generation around the whole design domain, there are still many demands for controlling local material proportion. This paper introduces a multi-volume constraint approach and its parameter configuration schemes to help users artificially pre-design the topologically optimized structure with the Bi-directional Evolutionary Structural Optimization (BESO) method. The numerical examples in this paper demonstrate that the presented method can be successfully applied in the computational structural form-finding for several building designs in various projects, e.g., high-rise building façades, circular shell domes, and nest-type stadium structures. It can provide the designers with diverse finely controlled structural layouts based on prescribed local material volume fractions. The structural performances of the diverse designs are very close to that of the globally optimal design. This study aims to make a bridge linking the computational optimization method to the human-centric design requirements, and it holds an enormous application potential in industrial or building designs.